Enhancement of dynamic phasor estimation‐based fault location algorithms for AC transmission lines. Issue 6 (10th February 2020) - Guillen, Daniel; Salas, Christian; Fernando Sanchez‐Gomez, Luis; Castro, Luis M.
Abstract : A new technique to improve fault location methods in AC transmission lines is introduced in this study. The identification of fault location is carried out using one‐end fault location algorithms based on impedance through dynamic phasors. This timely approach relies upon the fact that a fault resistance may introduce errors in the distance estimation when a fault takes place. Therefore, active power variations caused by the fault are used to enhance the fault location algorithms, i.e. power losses increase during the fault period for non‐zero fault resistances. The present approach is extensively evaluated, using ATP–EMPT software, which relies upon the computation of a compensation factor associated with the rate of change in the resistance during pre‐fault and fault conditions. This is achieved through the estimated phasors for voltage and current. Furthermore, the dynamic phasor estimation technique Taylor–Kalman–Fourier Filter is compared against a static phasor method. The proposed approach is validated using three fault location algorithms which are evaluated under different fault conditions, such as fault inception, location, and fault resistance. Results show that this proposed technique improves the fault location including fault resistances by 3% with respect to existing approaches.